The Moderating Effect of Organizational Culture on the Relationship Between Ethical Leadership And Spiritual Formation Among Church Members In Three Selected Districts of Wolaita Zone, Ethiopia - Eyob Denio Gifato (PAC University, 2025)
Spiritual formation is one of the major challenges facing the contemporary church, with organizational culture expected to play a critical role in the process of moderating this relationship. There is lack of ethical leadership and spiritual decline in the churches today; globally, regionally, and locally. The general objective of this study was to establish the moderating effect of organizational culture on the relationship between ethical leadership and spiritual formation among church members in three selected districts of Wolaita Zone, Ethiopia. The specific objectives of the study were: To determine the effect of respecting others, to explore the effect of serving others, to investigate the effect of justice, to examine the effect of honesty, to determine the effect of building community, and to explore the moderating effect of organizational culture on the relationship between ethical leadership and spiritual formation among church members. The study was anchored on the Ethical leadership Theory, Transformational leadership Theory, Servant Leadership Theory, and Path-goal Theory. This study was guided by the pragmatic research philosophy. It employed convergent parallel mixed method design. The target population of the study was 17,784 with a sample of 399. The study used simple random sampling techniques to select study participants. Open and closed ended questionnaires were administered to collect data for both quantitative and qualitative data. Validity and reliability of research instruments was established before conducting data collection. The findings of Cronbach’s Alpha test for reliability showed 0.90. For the validity test, the KMO measure of sampling value of 0.796 indicated a high level of reliability and validity of the study instrument. Data was analyzed using Statistical Package for the Social Science (SPSS) Version 30 for quantitative data. NVivo software was used for qualitative data. The results of the study indicated that respecting others correlated with spiritual formation at (R=0.162, P< .01), serving others at (R=0.282, P<.01), justice at (R=0.514, P <.01), honesty at (R= 0.214, P<.01), building community at (R= 0.492, P<.01. Analysis results revealed that the significant of the model of respecting others indicated (F- value of 10.274) and (β value .194), serving others (F-value of 33.095) and (β value .325), doing justice (F-value of 35.713) and (β value .336), building community (F-value of = 122.575) and (β value=.577), showed that the model was statistically significant. The significant of the model of honesty revealed (F-value of 2.268) and (β value .085) but (p-value =0.133) indicated that the model was statistically insignificant. The coefficients of determination of the moderating effect of organizational culture were 15.8% and 28.3% respectively. It brought 12.5% change in spiritual formation among church members. This study has a potential contribution to the body of knowledge in churches of Wolaita Zone, Ethiopia and beyond. The study recommends that the church leaders of three selected districts of Wolaita Zone, Ethiopia, should focus on spiritual formation among church members. Future studies could test other aspects of the study variables on the spiritual formation among church members in other regions.